2015
DOI: 10.1002/pc.23888
|View full text |Cite
|
Sign up to set email alerts
|

Durability study on glass fiber reinforced polymer soil nail via accelerated aging test and long‐term field test

Abstract: Replacing steel reinforcements with glass fiber reinforced polymer (GFRP) bars has emerged as one of the most promising solutions to the problem of corrosion in geotechnical engineering. Accelerated aging and field tests were conducted to investigate the durability of GFRP bars that were used as soil nails in slope reinforcement. Two types of E‐glass/(vinylester and unsaturated polyester) were immersed in alkaline and saline solutions for 60 d, 180 d and 360 d. Mechanical and physical experiments were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Numerous studies have focused on the environmental degradations of Polymer Matrix Composites (PMCs) in general, and more specifically, aging of Glass Reinforced Polymer (GRP) composites caused by a large variety of aggressive environments. Some of the most recent studies can be found in [1][2][3][4][5][6]. Very few of them, however, have dealt with the synergistic effects of aging of polymers and GRPs under combinations of several aging conditions [6,7 and 8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on the environmental degradations of Polymer Matrix Composites (PMCs) in general, and more specifically, aging of Glass Reinforced Polymer (GRP) composites caused by a large variety of aggressive environments. Some of the most recent studies can be found in [1][2][3][4][5][6]. Very few of them, however, have dealt with the synergistic effects of aging of polymers and GRPs under combinations of several aging conditions [6,7 and 8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it is believed that the harm of UVA to human cannot be ignored, because UVA has the strong ability to penetrate clothing and reach the dermis, not only destroying lipids and collagen and darkening human skin, but also leading to the DNA damage and cancer [16–19] . Besides the harms to human, UV radiation will accelerate the aging of organic and polymer materials and shorten their service time too [20–24] . Therefore, protection of people and materials from UV irradiation is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] There are three main mechanisms, which govern the water absorption in a GFRP composite: water diffusion into polymer matrix, diffusion at the interfaces of fiber/matrix, and capillary uptake by voids, while water uptake by glass fibers is quite insignificant. [7] The absorbed water primarily affects the state of the polymeric matrix and fiber/matrix interphase regions by inducing both irreversible and reversible alterations in the microstructure of the matrix through plasticization, hydrolysis, or saponification, thereby adversely affecting their mechanical, chemical, and thermophysical properties. [8] In the past several years, different research groups have attempted to study the durability and performance of glass fiber laminated composites when exposed to various water media, such as distilled water, tap water, seawater, and so on.. [9] Aldajah et al [10] have reported reductions of 60% and 55% in the flexural stiffness of symmetric GFRP composite laminates when subjected to tap water and sea water conditioning, respectively, for 2000 hours.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3–6 ] There are three main mechanisms, which govern the water absorption in a GFRP composite: water diffusion into polymer matrix, diffusion at the interfaces of fiber/matrix, and capillary uptake by voids, while water uptake by glass fibers is quite insignificant. [ 7 ] The absorbed water primarily affects the state of the polymeric matrix and fiber/matrix interphase regions by inducing both irreversible and reversible alterations in the microstructure of the matrix through plasticization, hydrolysis, or saponification, thereby adversely affecting their mechanical, chemical, and thermophysical properties. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%